2019
DOI: 10.3390/ijms20030566
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Onset of Age-Dependent Changes in Ultrastructure of Myocardial Mitochondria as One of the Neotenic Features in Naked Mole Rats (Heterocephalus glaber)

Abstract: In this study, the ultrastructure of mitochondria in cardiomyocytes of naked mole rats (Heterocephalus glaber) aged from 6 months to 11 years was examined. Mitochondria in cardiomyocytes of naked mole rats have a specific ultrastructure that is different from those in cardiomyocytes of other mammalian species studied to date. In contrast to mitochondria of other mammalian cardiomyocytes, where the internal space is completely filled by tightly packed parallel rows of cristae, mitochondria in cardiomyocytes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…Several studies have documented alterations in mitochondrial function [16,42] and morphology [58,59] in mole-rats, which our results support from an epigenomic perspective. Moreover, we found lineage-specific liver enhancers in mole-rats enrich for SINE repeat families and associate with fatty acid oxidation processes, which is in agreement with the reported increase in fatty acid utilization in mole-rat liver [16].…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have documented alterations in mitochondrial function [16,42] and morphology [58,59] in mole-rats, which our results support from an epigenomic perspective. Moreover, we found lineage-specific liver enhancers in mole-rats enrich for SINE repeat families and associate with fatty acid oxidation processes, which is in agreement with the reported increase in fatty acid utilization in mole-rat liver [16].…”
Section: Discussionsupporting
confidence: 87%
“…The naked mole-rat is a long-lived species having a life span that can exceed 30 years 1,2 , which is nearly ten times longer than that of rodents of comparable size. Possessing many neotenic features 3,4 and defying many of the signs of ageing 5 , the naked mole-rat does not appear to develop neurodegenerative disease 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…The whole intermembrane space of the mitochondrion is filled with cristae in the form of curled, wave-like structures (indicated by arrows). It should be noted that previously we found mitochondria of similar ultrastructure in cardiomyocytes of naked mole rat aged above 5 years [ 34 ].…”
Section: Resultsmentioning
confidence: 73%
“…The available literature lacks data on the ultrastructural study of naked mole rat tissues except for the study by Onyango et al [ 32 ] performed using the testis of naked mole rat, and the work of Stoll et al [ 33 ] in which selected electron microscopic images are provided for illustration of histological and functional characteristics of naked mole rat. Our investigations [ 34 ] of the mitochondrial ultrastructure of cardiomyocytes of naked mole rat demonstrated that by the age of 11 years their mitochondria do not show any abnormalities. The mitochondrial ultrastructure corresponds to the phenotype of young animal which is one of the neotenic features in naked mole rat.…”
Section: Introductionmentioning
confidence: 91%